Estrategias de marketing de la Cadena Alimenticia Cheese & Cheese de la ciudad de Babahoyo - Sanchez Garofalo, Tania Stefania (2021)
The Cheese & Cheese food chain located in the city of Babahoyo, Los Rios Province, is a micro-company that has several branches, which began in 2007, its main economic activity is the sale of fast food, which in recent years has shown great growth. The owner and administrator of this enterprise aims to increase the branches as well as generate sources of employment to contribute to the economy, adopt new marketing strategies for the proper functioning of the business. The main objective of this case study is to present the marketing strategies that failed and the marketing strategies that have been favorable and have generated productivity in the food chain called Cheese & Cheese.